Acute Kidney Injury in Diabetic Patients With Acute Myocardial Infarction: Role of Acute and Chronic Glycemia. Issue 8 (13th April 2018) - Marenzi, Giancarlo; Cosentino, Nicola; Milazzo, Valentina; De Metrio, Monica; Rubino, Mara; Campodonico, Jeness; Moltrasio, Marco; Marana, Ivana; Grazi, Marco; Lauri, Gianfranco; Bonomi, Alice; Barbieri, Simone; et al.
Abstract : Background: In acute myocardial infarction, acute hyperglycemia is a predictor of acute kidney injury (AKI), particularly in patients without diabetes mellitus. This emphasizes the importance of an acute glycemic rise rather than glycemia level at admission. We investigated whether, in diabetic patients with acute myocardial infarction, the combined evaluation of acute and chronic glycemic levels may have better prognostic value for AKI than admission glycemia. Methods and Results: At admission, we prospectively measured glycemia and estimated average chronic glucose levels (mg/dL) using glycosylated hemoglobin (HbA1c ), according to the following formula: 28.7×HbA1c (%)−46.7. We evaluated the association with AKI of the acute/chronic glycemic ratio and of the difference between acute and chronic glycemia (ΔA−C ). We enrolled 474 diabetic patients with acute myocardial infarction. Of them, 77 (16%) experienced AKI. The incidence of AKI increased in parallel with the acute/chronic glycemic ratio (12%, 14%, 22%; P =0.02 for trend) and ΔA−C (13%, 13%, 23%; P =0.01) but not with admission glycemic tertiles ( P =0.22). At receiver operating characteristic analysis, the acute/chronic glycemic ratio (area under the curve: 0.62 [95% confidence interval, 0.55–0.69]; P =0.001) and ΔA−C (area under the curve: 0.62 [95% confidence interval, 0.54–0.69]; P =0.002) accurately predicted AKI, without difference in the area under the curve between them ( P =0.53). At reclassification analysis, the addition of the acute/chronic glycemic ratio and ΔA−C to acute glycemia allowed proper AKI risk prediction in 16% of patients. Conclusions: In diabetic patients with acute myocardial infarction, AKI is better predicted by the combined evaluation of acute and chronic glycemic values than by assessment of admission glycemia alone.